Anne of Windy Poplars - Montgomery, L. M. (Lucy Maud), 1874-1942 (Montgomery, L. M. (Lucy Maud), 1874-1942. Anne of Green Gables novels, 1998)
Anne Shirley's love for Gilbert Blythe grows during her three years as a high school principal.